Biofertilizante como ferramenta para incrementar a diversidade microbiana visando o manejo de doenças de plantas - Machado, Maria Augusta de Camargo Ferraz (Universidade Federal de São Carlos, 2010)
In this study were compared the community of yeasts in the phylloplane of lily a conventional system with high pesticide use, with an without pesticide use, with the use of biofertilizers and biocontrol agents; to evaluate the antagonism of yeast Sporidiobolus pararoseus isolated from leaves of lily on Botrytis cinerea; determined the microbial epiphytic in plant lily conventional and without pesticide use systems; characterized microbiological two biofertilizers produced aerobically, one from compost, earthworm-compost, yeast and molasses, and another from swine manure, poultry litter, bone meal and sugar; evaluated the effect of biofertilizers on plant growth-promoting and on the control of pathogens. We observed: the population of bacteria, Bacillus, yeasts and fungi in plants of lily conducted in the conventional system with high pesticide use is low and the population of these organisms is higher in plants cultivated in system without use of pesticides; S. pararoseus is the main component of the microbial community of the lily phyloplane in leaves treated with biofertilizer; S. pararoseus has potential in reducing the incidence and severity of B. cinerea and is essential to maintain a high population to act in the natural of biological control of the disease; biofertilizers as well as organic materials used in production have the potential to control pathogens; swine manure showed higher efficacy in reducing the mycelial growth of Pythium; biofertilizers promoted growth in the plants with the presence of NPK; biofertilizers did not control powdery mildew on zucchini squash, indicating that the effect of biofertilizers on plant diseases depends on the organic material and pathosystem.
Biofertilizer as tool to increase microbial diversity for management of plants diseases
Keywords: Controle biológico; Biofertilizantes; Matéria orgânica; Levedura; CIENCIAS AGRARIAS